Potentially inappropriate medication use in older adults with mild-moderate Alzheimer's disease: prevalence and associations with adverse events. (30th May 2020) - Murphy, Claire; Dyer, Adam H; Lawlor, Brian; Kennelly, Sean P; ,
Abstract: Aim: Potentially inappropriate medication (PIM) use is prevalent in older adults and is associated with adverse events, hospitalisation and mortality. We assessed the patterns and associations of PIM use in older adults with mild-to-moderate Alzheimer's Disease (AD), who may represent a particularly vulnerable group. Design: Analysis of data from NILVad, an 18-month Randomised Control Trial of Nilvadapine in mild-to-moderate AD. The v2 STOPP criteria were applied in duplicate to identify PIM use. Associations between PIM use and adverse events/unscheduled healthcare visits in addition to the associations between PIM use and AD progression were evaluated. Setting and Participants: 448 older adults with mild-to-moderate AD from 23 centres in nine European countries. Results: Of 448 participants (mean age: 72.56 ± 8.19 years), over half (55.8%) were prescribed a PIM with 30.1% being prescribed 2+ PIMs. The most frequent PIMs were (i) long-term benzodiazepines (11.6% N = 52/448), (ii) selective serotonin reuptake inhibitors without appropriate indication (11.1% N = 50/448), and (iii) Proton-Pump Inhibitors (PPIs) without appropriate indication (10.7% N = 48/448). Increasing number of PIMs was associated with a greater risk of adverse events (IRR 1.17, 1.13–1.19, P < 0.001), serious adverse events (IRR 1.27; 1.17–1.37, P < 0.001), unscheduled hospitalisations (IRR 1.16, 1.03–1.30, P = 0.016) and GP visits (IRR 1.22, 1.15–1.28, P < 0.001). PIM use was not associated with dementia progression. Conclusions and Implications: PIM use is highly prevalent in mild-to-moderate AD and is associated with adverse events and unscheduled healthcare utilisation. Further attention to de-prescribing in this vulnerable group is warranted.